2010
DOI: 10.1007/s10509-010-0464-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of equilibrium points in the generalized perturbed restricted three-body problem

Abstract: This paper studies the existence and stability of equilibrium points under the influence of small perturbations in the Coriolis and the centrifugal forces, together with the non-sphericity of the primaries. The problem is generalized in the sense that the bigger and smaller primaries are respectively triaxial and oblate spheroidal bodies. It is found that the locations of equilibrium points are affected by the non-sphericity of the bodies and the change in the centrifugal force. It is also seen that the triang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 13 publications
(24 reference statements)
2
15
0
Order By: Relevance
“…They are seen to be affected by the shape of the participating bodies and their orbital geometries. These results agree with [27] in the absence of oblateness and with [37] in the circular case. The collinear points also remain unstable due to the presence of real roots and despite the introduction of the triaxiality and oblateness parameters.…”
Section: Resultssupporting
confidence: 86%
“…They are seen to be affected by the shape of the participating bodies and their orbital geometries. These results agree with [27] in the absence of oblateness and with [37] in the circular case. The collinear points also remain unstable due to the presence of real roots and despite the introduction of the triaxiality and oblateness parameters.…”
Section: Resultssupporting
confidence: 86%
“…In the second coefficient of (10), the term containing a small change in the centrifugal in AbdulRaheem and Singh [2] are different while the other terms are same with ours. In Singh and Begha [18], the all the terms there are a found in ours when 2 1 σ σ = . In the third coefficient, our results are in accordance with that in AbdulRaheem and Singh [2] but again the term containing the small change, differs.…”
Section: Discussionsupporting
confidence: 48%
“…We note that the first coefficient in the equation are same with that in AbdulRaheem and Singh [2], except for what seems like a typographic error in the coefficient of the oblateness of the bigger primary. However, the coefficients of the term containing triaxiality of the bigger primary in the paper by Singh and Begha [18] are equally erroneous. In the second coefficient of (10), the term containing a small change in the centrifugal in AbdulRaheem and Singh [2] are different while the other terms are same with ours.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The stability is actually achieved through the influence of the Coriolis force, because the coordinate system is rotating (Wintner [2]; Contopolous [3]). Various contributions (Szebehely [4]; Bhatnagar and Hallan [5]; AbdulRaheem and Singh [6]; Singh and Begha [7]; and Abouelmagd et al [8]) have been made on the study of the restricted three-body problem under the effects of small perturbations in the centrifugal and Coriolis forces. Szebehely [4] investigated the stability of triangular points by keeping the centrifugal force constant and found that the Coriolis force is a stabilizing force.…”
Section:  mentioning
confidence: 99%